THE ANALYSIS OF SKIMMING AND SCANNING TECHNIQUE TO IMPROVE STUDENTS IN TEACHING READING COMPREHENSION - Intan Rani Aritonang; Sandi Lasmana; Deti Kurnia (PROJECT (Professional Journal of English Education), 2018)
This research deals with The Analysis of Skimming and Scanning Technique to Improve Students Teaching Reading Comprehension. This research explores the implementation of Skimming and Scanning in reading comprehension and to find out the advantages and disadvantages of skimming and scanning used in learning process. The objective of this research is to find out the effectiveness of skimming and scanning strategy in improving students reading comprehension. Data collection technique focus on participant observation, interviews, and documentation. Skimming and Scanning is the appropriate technique to find the main idea, key word and content of the text without read the whole of the text.